Nitrosilo complexos de rutênio com ligantes bifosfínicos: espectroscopia, eletroquímica, estudo da reatividade e liberação de NO - Poelhsitz, Gustavo Von (2005)
In this thesis some series of ruthenium nitrosyl complexes presenting as common characteristic the presence of diphosphines ligands in their structures, among them: dppm, dppe, c-dppen, dppp, dppb, dcpe and dppf were studied. It was sought in each series to evaluate the electronic properties of the coordinated NO as a function of the changes in the diphosphine ligand as well as to compare the NO properties among the series, in this case the characteristics of the other co-ligands were considered. The usual techniques were used to characterize the complexes: IR, UV/vis, NMR and for some compounds 15N{1H}NMR spectroscopies, mass spectrometry, cyclic voltammetry, differential pulse voltammetry and elemental analysis. For some compounds single crystals appropriated to X-ray diffraction analysis were obtained, leading to a valuable structural study. Specifically, in this work the mer-[RuCl3(NO)(P-P)], P-P = diphosphine, series was synthesized by the photochemical isomerization of the corresponding fac isomers in CH2Cl2 solution or in the solid state. The synthesis and NMR characterization of the mer-[RuCl3(15NO)(dppb)] allowed the correct attribution of the signal corresponding to each phosphorus in the 31P{1H} NMR spectra of the mer series. The electrochemical study shows that the oxidation/reduction processes observed in these complexes are dependent on both, the isomer (fac or mer) and the solvent. In CH2Cl2 the NO+ reduction potentials are less negative for the mer-isomers than for the fac, while in CH3CN these potentials are, in general, very close for both isomers. The reactions products of the fac-[RuCl3(NO)(P P)], P P = dppe or c-dppen, with the 4,6-dimethyl-2-mercaptopyrimidine ligand in methanol were the nitrosyl [Ru( SpymMe2 ,-N,-S)( SpymMe2 ,-S)(NO)(P P)]PF6, these were the first ruthenium complexes containing the nitrosyl and a pyrimidine derivative ligands. For these species, the cyclic voltammograms showed the first NO+ reduction reversible at @ -0.35 V and an irreversible process for the second reduction at @ -1.1 V. The trans-[RuCl(NO)(dppe)2]2+ complex had its photochemical behavior evaluated at 355 nm in CH3CN NO labilization (confirmed by a selective electrode) and formation of RuII and RuIII species identified by 31P{1H} NMR and EPR, respectively, were found. The same photochemical experiment carried out in CH2Cl2 produced species containing the RuII-NO0 unit as well as RuIII that were identified by EPR. With the same compound NO labilization was obtained with 520 nm irradiation by utilizing rhodamine B as sensitizator. The NO+ character of the trans-[RuCl(NO)(P-P)2]2+, P-P = dppe or c-dppen, complexes was evaluated by the reaction with the azide nucleophile in CH3CN forming the corresponding solvento derivatives. Complexes with general formula [RuCl(NO)(dcpe)(NN)] 2+, N-N = bipy, Me-bipy or phen, were synthesized and characterized showing an nNO close to 1890 cm-1 and a reversible pair NO+/NO0 with E1/2 close to 0.1 V. The geometry of these complexes were determined by the 31P{1H} NMR spectrum of the [RuCl(15NO)(dcpe)(bipy)]2+ species that showed one of the phosphorus trans to the NO, consequently the other one is trans to nitrogen. It was also shown that these complexes are attacked by the azide ion and that photo-induced NO labilization occurs in CH3CN when solutions are exposed to white light.